38 THE POTENTIAL OF CYCLIC VOMITING SYNDROME AS A DEVELOPMENTAL ANOMALY OF THE BRAIN. (1st January 2005) - Stone, M.; Adams, K.; Boles, R.
Abstract : Cyclic Vomiting Syndrome (CVS) is a disease affecting predominantly children. It is characterized by cycles of vomiting, nausea and lethargy. The syndrome is idiopathic, although known associations include migraine headache, dysautonomia and mitochondrial dysfunction. It is possible that a developmental defect of the brain is the underlying cause for vomiting episodes, at least in some individuals. If this is the case, these individuals may also present with a higher prevalence of other developmental anomalies and chromosomal aneuploidies than is found in the general population. A questionnaire was administered to 108 CVS sufferers who were randomly selected from the registry of the Cyclic Vomiting Syndrome Association USA/Canada. Six of these subjects (6%) carried diagnoses consistent with aneuploidy, including abnormalities of chromosome 18 (3 cases), Down syndrome (2) and Kabuki syndrome (1). An additional 12 CVS subjects out of 80 (15%) who completed the study reported the presence of at least one major congenital malformation, versus about 3% in most population-based surveys (P = 8x10-7). Combined, 18 of 108 subjects (17%) have congenital malformations. We conclude that CVS patients present with an increased prevalence of both aneuploidy and congenital malformations. This supports that notion that a developmental anomaly of the brain may play a key role in the disease of some CVS sufferers. In the appropriate clinical setting, co-morbid findings may indicate performing a chromosomal analysis and/or a work-up for undiagnosed birth defects.